Comparison of serum triglyceride levels with propofol in long chain triglyceride and propofol in medium and long chain triglyceride after short term anesthesia in pediatric patients - Ishwar Bhukal; Gokul Thimmarayan; Indu Bala; Sohan Lal Solanki; Tanvir Samra (Saudi Journal of Anaesthesia, 2014)
Background: Significant increase in serum triglyceride (ST) concentration have been described in adult population after prolonged administration of propofol formulation containing long chain triglyceride (LCT). Though, medium chain triglyceride-LCT (MCT-LCT) propofol when compared with LCT propofol for long-term sedation in adults resulted in identical triglyceride levels, the elimination of triglyceride was faster in patients administered MCT-LCT propofol. Materials and Methods: A total of 40 children were randomized into two groups of 20 each; Group I were induced with 1% LCT propofol (3 mg/kg) and Group II with 1% medium and LCT propofol and maintained with descalating dose of 20.15 and 10 mg/kg/h at 10 min intervals. Blood samples for ST concentration were obtained before induction of anesthesia, at the end of propofol infusion and 4 h after terminating propofol infusion. Results: ST levels were raised significantly above the basal values in both the groups but the rise was significantly higher in Group I (P < 0.05). Four hours after stopping propofol infusion the triglyceride levels were similar to the basal values in Group II, whereas in Group I the values were significantly greater than the baseline (P < 0.05) as well as those of Group II (P < 0.05). No clinically significant adverse effect of hypertriglyceridemia was observed. Conclusion: Even short term anesthesia with LCT and MCT-LCT propofol (1%) leads to elevated ST levels. The increase in ST levels is less with MCT-LCT propofol and elimination of triglyceride is also rapid after terminating MCT-LCT propofol infusion.